Guided Bilateral Transcanine Implant Placement and Implant-Supported Oral Rehabilitation in a Patient with Progressive Systemic Scleroderma - Igor Smojver; Ivan Katalinić; Marko Vuletić; Luka Stojić; Dražena Gerbl; Dragana Gabrić (Case Reports in Dentistry)
When faced with a situation where an impacted tooth is in the way of a planned implant, one approach to avoid an invasive surgical procedure and potential associated complications is to place a transcanine implant. The aim of this report was to add a new case of a transimpacted tooth dental implant placement to the existing international literature and to share our experience of transcanine implantation in the maxilla followed by implant prosthodontic rehabilitation of a patient with progressive systemic scleroderma. A 55-year-old woman attended our office for oral cavity assessment and treatment planning for complete oral rehabilitation. Digital planning software was used, and implants were positioned according to a surgical template in regions 13, 16, 23, and 26 (Straumann, Basel, Switzerland) with screw-retained metal-ceramic bridges. Placement of the dental implants through impacted canines and the creation of interfaces other than implant-bone interfaces did not lead to postoperative pain or implant failure. Clinically, overall healing was observed, and the implants were successfully used for implant-supported prosthodontic rehabilitation of the jaw. Within the limitations of this case report, transcanine implantation could represent a valuable alternative to standard implant protocols.